Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d1ew00700a
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol-driven denitratation: process kinetics, microbial ecology, and operational controls

Abstract: Denitratation, the selective reduction of nitrate to nitrite, is a novel process when coupled with anaerobic ammonium oxidation (anammox) could achieve resource-efficient biological nitrogen removal of ammonium- and nitrate-laden waste...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…The glycerol PdN efficiency was consistent with previous studies, 21,26,34–38 showing the reproducibility of the PdNA process. The methanol PdN efficiency obtained in this study was higher than the PdN efficiency obtained in the methanol-fed full-scale PdNA filter owing to the higher loading rates in this study (450 g NO 3 − -N m −3 d −1 vs. 110 g NO 3 − -N m −3 d −1 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The glycerol PdN efficiency was consistent with previous studies, 21,26,34–38 showing the reproducibility of the PdNA process. The methanol PdN efficiency obtained in this study was higher than the PdN efficiency obtained in the methanol-fed full-scale PdNA filter owing to the higher loading rates in this study (450 g NO 3 − -N m −3 d −1 vs. 110 g NO 3 − -N m −3 d −1 ).…”
Section: Resultssupporting
confidence: 91%
“…21 The lower PdN efficiency in the methanol-fed filter was most likely attributed to the difference in electron competition mechanism 33 and lower rate differential between nitrate and nitrite reduction. 18 The glycerol PdN efficiency was consistent with previous studies, 21,26,[34][35][36][37][38] showing the reproducibility of the PdNA process. The methanol PdN efficiency obtained in this study was higher than the PdN efficiency obtained in the methanol-fed full-scale PdNA filter owing to the higher loading rates in this study (450 g NO 3…”
Section: Impact Of Carbon Source Onsupporting
confidence: 89%
“…Several studies have pointed to the Thauera species as a source for this progressive onset concept. 41,47–50…”
Section: Resultsmentioning
confidence: 99%
“…16,21,22 Studies have shown the ability of glycerol and acetate to induce significant nitrite accumulation. 21,22,34,41 Methanol, acetic acid, and glucose resulted in 17%, 21%, and 23% NO 2 -N accumulation with a low COD/NO 3 -N. 24 In another study, glycerol, acetate, and methanol were all capable of performing PdN, but glycerol and acetate displayed more efficient PdN than methanol and this was attributed to their different electron transport pathways. 16 The sCOD added per TIN removed for each phase was 2.41 ± 0.98, 2.02 ± 0.71, and 1.73 ± 0.81 g COD g N −1 for glycerol, acetate and methanol respectively (Table 2).…”
Section: Pdn Efficiency and Carbon Requirementsmentioning
confidence: 99%
See 1 more Smart Citation